Land Suitability Evaluation for Cereal Crops: A Multicriteria Approach Using GIS at Parbatipur VDC, Chitwan, Nepal - Neupane, B.; Shriwastav, C.P.; Shah, S.C.; Sah, K. (International Journal of Applied Sciences and Biotechnology, 2014)
A research was conducted to evaluate the suitability of soils of different land unit for cereal crops productions at Parbatipur VDC, Chitwan, Nepal with the integrated use of Geographical Information system (GIS) and Multi-criteria evaluation (MCE).Existing geodatabase information from National Land Use Project (NLUP) was used as data for this research. The database was used to derive crop suitability using vector based index model in GIS along with multi-criteria analysis. The research revealed that for rice cultivation, 1.06 %( 10.70ha) was highly suitable, 51.54 %( 515.89ha) was moderately suitable, 3.39% (33.987 ha) was marginally suitable but 28.28 %( 283.11 ha) was not suitable whereas for wheat cultivation, 7.6 %( 76.73ha) was highly suitable, 44.91% (449.53 ha) was moderately suitable and 4.6% (46.26ha) was marginally suitable, but 27.15% (27.14ha) was not suitable. Similarly, for maize cultivation, 12.07% (120.83ha) was highly suitable, 40.19% (402.25ha) was moderately suitable and 0.53% (5.37ha) was marginally suitable, but 31.54% (315.72ha) was not suitable for maize production. Suitability data of this VDC shows that maize and wheat was highly suitable than rice cultivation. But, the area not suitable for rice, wheat and maize must be allocated for alternative uses to achieve optimum productions and further there must be new research for alternative crops in VDC. Hence, this research is useful to farmers and VDC level planners for optimum crops production. DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11279Int J Appl Sci Biotechnol, Vol. 2(4): 493-500